PENGETAHUAN TENTANG MEMBANGUN RESILIENSI KELUARGA KETIKA MENGHADAPI PANDEMI COVID-19 - Kristiyani, Veronica; Khatimah, Khusnul (Universitas Esa Unggul, 2020)
The current condition of the Covid-19 pandemic which has an impact on financial, health, education and other aspects makes families need to support each other so that they can develop resilience in the family. The purpose of community service carried out within the scope of Esa Unggul University lecturers is to provide knowledge about building family resilience during the Covid-19 pandemic. The implementation method is carried out through laptop electronic devices and through the Zoom application with the speaker distributing slides through Zoom and then a discussion is held in the form of questions and answers to increase the participants' understanding. As a result, most of the participants considered this community service activity very important and very beneficial, but a small proportion considered it the opposite. In the future, it is hoped that community service activities will be held with topics related to family resilience but focused on tips or ways that participants can do. In addition, a guidebook can also be made regarding ways to increase family resilience so that it can be used by participants and the wider community.Ã‚Â Keywords: family resilience, covid-19 pandemic, challenges